Mohs Surgery versus Standard Local Excision for Basal Cell Carcinoma, Squamous Cell Carcinoma, and Melanoma Skin Cancer - Johnson, Timothy M.; Smith, Noah R. (Facial Plastic Surgery, 2020)
Basal cell carcinoma, squamous cell carcinoma, and melanoma represent the three most common skin cancers that occur on the face. The most common surgical treatments for facial skin cancers are Mohs surgery and standard local excision. The effective utilization of either of these techniques is based on tumor and patient risk stratification incorporating known risk factors for occult invasion and local recurrence, combined with patient comorbidities, expectations, and desires. Best available evidence highlights multiple and consistent risk factors for each specific skin cancer type, and dictate local control rates reported in the literature. Recognizing gaps in the literature, we compare and review surgical treatment guidelines and data for standard local excision versus Mohs surgery for cutaneous nonmelanoma and melanoma skin cancer. This article serves as a resource for optimal therapeutic decision making for surgical management of skin cancer on the face.
Keywords: basal cell carcinoma; squamous cell carcinoma; melanoma; Mohs surgery; standard local excision